Review of IFRS consequences in Europe: An enforcement perspective - Geraroid O Cualain; Vincent Tawiah (Cogent Business & Management)
The purpose of this paper is to review existing literature on the consequences of International Financial Reporting Standards (IFRS) adoption in Europe with a specific focus on different enforcement environments. Following prior studies, we adopt the critical review approach. We begin the review in Europe and then provide a comparative analysis among four countries based on their enforcement environment. Academic papers were collected from high-quality ranked journals. The literature was analysed on different streams, including comparability, audit services liquidity and earning management. Our critical review indicates that the consequences of IFRS adoption depend on the country’s enforcement environment. If a country has strong enforcement, then the consequences of IFRS adoption are more pronounced for both positive and negative consequences. This was the case for the UK and Germany. If a country has a weak enforcement environment, the consequences are less pronounced, as was the case for Spain and Italy. The consequences of IFRS adoption include increased comparability, audit fees, liquidity, earnings management and investment. If a country is to realise the benefits of IFRS adoption fully, it is not sufficient to just adopt the standards; there must be a strong enforcement environment. The paper makes suggestions for further research in the context of IFRS consequences.